Accuracy of Using Digital, Mercury and Aneroid Sphygmomanometer - Novian Aldo; Dewi Puspa Rianda; Muthia Deliana; Indah Dwi Astuti (Aloha International Journal of Health Advancement (AIJHA), 2022)
Blood pressure is an essential factor in the human body's circulatory system. Blood pressure is the pressure felt by the artery walls when blood is pumped by the heart throughout the body. The instrument used to measure blood pressure is a sphygmomanometer. The sphygmomanometer used to work manually, but now it works automatically using digital. The accuracy of the digital sphygmomanometer measurement depends on the battery life. The brand of digital or mercury sphygmomanometer and periodic calibration can also affect the measurement results. The purpose of this study was to see the accuracy of using a digital, mercury, and aneroid sphygmomanometer for the residents of the Rumah Bahagia Bintan Elderly Nursing Home and the Health Polytechnic of Tanjungpinang students in 2019. The design of this study was observational with a cross-sectional research design. The sample used in this study were 30 residents of Rumah Bahagia Bintan Elderly Nursing Home and 30 first-year students of Health Polytechnic of Tanjungpinang. Data were collected by measuring blood pressure with a digital, mercury, and aneroid sphygmomanometer 3 times with an examination interval of 5 minutes. The data analysis used the Mann-Whitney Test because the data were normally distributed with a significance of 5%. The study showed no difference between systolic and diastolic blood pressure using a digital, mercury, and aneroid sphygmomanometer. Keywords: mercury sphygmomanometer; digital sphygmomanometer; aneroid sphygmomanometer; blood pressure